2015
DOI: 10.1021/cm504202v
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Strategies for Tailoring the Physicochemical and Magnetic Properties of Hydrophobic Magnetic Ionic Liquids

Abstract: Magnetic ionic liquids (MILs) are a subclass of ionic liquids (ILs) containing paramagnetic components and are readily manipulated by an external magnetic field. Due to their hydrophilic nature, very few applications of MILs in aqueous systems have been reported. In this study, three general classes of hydrophobic MILs including monocationic, symmetrical/unsymmetrical dicationic, and symmetrical/unsymmetrical tricationic MILs were synthesized and characterized. By tuning the structure of the MIL, various physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 33 publications
1
68
0
Order By: Relevance
“…The halide counteranion was then exchanged to [FeCl 3 Br] − using equimolar amounts of iron(III) chloride hexahydrate in methanol to obtain IL 1. ILs 2, 4-10 were synthesized following previously reported procedures [32,33]. The synthetic route for the dication platform is shown in Fig.…”
Section: Synthesis Of Dicationic Ionic Liquidsmentioning
confidence: 99%
“…The halide counteranion was then exchanged to [FeCl 3 Br] − using equimolar amounts of iron(III) chloride hexahydrate in methanol to obtain IL 1. ILs 2, 4-10 were synthesized following previously reported procedures [32,33]. The synthetic route for the dication platform is shown in Fig.…”
Section: Synthesis Of Dicationic Ionic Liquidsmentioning
confidence: 99%
“…Analytes were readily introduced to the HS within aerosol droplets to facilitate rapid mass transfer into the IL extraction solvent. Yang et al found that analyte recoveries for the UNE-HS-IL-SDME method were comparable to a traditional hydrodistillation method using the [C 8 MIM + ][PF 6 − ] IL. Jiang et al demonstrated the benefit of using UNE-HS-IL-SDME to afford shorter extraction times (i.e., 25 min) relative to HS-SPME and stir-bar sorptive extraction (approx.…”
Section: Ionic Liquids In Single Drop Microextractionmentioning
confidence: 99%
“…The chlorophenols were detected using HPLC with a dual wavelength detector. Another study used the [C 8 MIM + ][PF 6 − ] IL for the preconcentration of kanamycin sulfate before detection using electrochemiluminescence [34]. Wang et al investigated the extraction of three phthalate esters using the [C 4 MIM + ][PF 6 − ] as the acceptor phase and 1-nonanol as the extraction phase in a HF-LPME method [35].…”
Section: Ionic Liquids In Hollow Fiber Membrane Liquid-phase Microextmentioning
confidence: 99%
See 2 more Smart Citations